A Study of Criticism Strategies in a British Reality Show “The Great British Bake Off Season 11”: การศึกษากลวิธีการวิจารณ์ในรายการเรียลลิตี้โชว์สัญชาติอังกฤษ “The Great British Bake Off ปีที่ 11” - Auewong, Pakjira; Rhekhalilit, Kittinata (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2023)
The purpose of this study was to examine the pragmatic strategies of critique within the setting of a television program. This study collected data of the British judges’ criticism comments from five episodes of Season 11 of The Great British Bake Off, which contained 100 commenting sequences. The analytical framework was derived from criticism-related studies that divided criticism into direct and indirect categories. The findings indicated that direct types were employed more frequently than the indirect ones. British judges most frequently employed the sub-strategy of expressing a negative attitude while delivering direct criticism, emphasizing the judge’s choice and generating a sense of authority. For the application of indirect criticism, the judges utilized both the sub-strategy of expressing an expectation and suggestion. The first method avoided direct confrontation by asserting that the outcome differed from the judge’s expectations, while the second strategy offered positive suggestions for the contestant’s future growth. In particular, it was hypothesized that the results of the criticism strategies were influenced by both the position of the competition program’s judges and politeness. This research contributes to the existing criticism and media literature.